Contents of black carbon in some anthrosols from Zhejiang Province - LIU Zhao-yun; ZHANG Ming-kui (浙江大学学报. 农业与生命科学版)
To understand the effects of human activity on accumulation of black carbon in soils, 251 surface soil samples were collected from Zhejiang Province. The soil samples had different land uses, including urban green space, road in urban area, manufacture area, vegetable land in suburban area, upland in countryside, and paddy field in countryside. The contents of black carbon in the samples were characterized by chemical method. The contents of black carbon in the soils ranged from 0 to 15.22 g·kg-1, and averaged 3.83 g·kg-1. Most samples (70.92%) had black carbon ranging from 1 to 5 g·kg-1. Mean contents of black carbon in the soils for different land uses decreased in the sequence of manufacture area > vegetable land in suburban area > road in urban area > upland in countryside area > green space in urban area> paddy field in countryside. Proportion of black carbon in total organic carbon ranged from 0% to 53.20% with mean of 24.83%. The proportion decreased in the sequence of manufacture area > road in urban area > vegetable land in suburban area > urban green space > upland in countryside > paddy field in countryside. Correlation analysis showed that contents of soil black carbon were positively and significantly correlated with its total organic carbon, and the proportions of black carbon in the soil total organic carbon were positively and significantly correlated with their black carbon contents, and insignificantly correlated with the total organic carbon content.